CENTRAL NERVOUS SYSTEM INVOLVEMENT IN PEDIATRIC HEMOLYTIC UREMIC SYNDROME: FREQUENCY, IMAGING PATTERNS, AND CLINICAL OUTCOMES - Barbara Wardzyńska; Jolanta Barbara Mataśka; Natalia Sałkowska; Eliza Mędrek; Natalia Brzozowska; Jakub Magdziak; Oliwia Borowska; Sara Awad; Paulina Zegarska; Hanna Markowska (International Journal of Innovative Technologies in Social Science, 2026)
Background: Hemolytic uremic syndrome (HUS) is the leading cause of typical thrombotic microangiopathy in children, most commonly triggered by Shiga toxin–producing Escherichia coli (STEC). Beyond the classic triad of microangiopathic hemolytic anemia, thrombocytopenia, and acute kidney injury, central nervous system (CNS) involvement is a major determinant of severity.Methods: Narrative synthesis of clinical, epidemiologic, and neurodiagnostic literature addressing pediatric HUS with CNS involvement.Results: Neurological complications in STEC-HUS occur in approximately the low-teens in contemporary cohorts and most often present with seizures and encephalopathy; PRES, focal deficits, movement disorders, and cerebrovascular complications are less frequent but clinically significant. STEC-HUS is initiated by Shiga toxin–mediated endothelial injury leading to thromboinflammation and microvascular thrombosis, while complement activation likely amplifies endothelial damage and contributes to CNS vulnerability. In aHUS, neurological involvement is more frequent and reflects systemic complement-mediated microangiopathy. MRI, particularly diffusion-weighted imaging and ADC mapping helps differentiate microangiopathic injury from PRES or infarction/hemorrhage and may support early risk stratification. EEG is useful for detecting epileptic activity and subclinical encephalopathy. Management is predominantly supportive and neurocritical (seizure control, blood pressure management, correction of metabolic derangements, and renal support). Eculizumab is essential in aHUS but remains controversial in STEC-HUS, with no consistent neurological benefit over standard care in recent syntheses.Conclusions: CNS involvement identifies a high-risk pediatric HUS subgroup requiring early neurologic assessment, targeted MRI/EEG use, meticulous critical care, and structured long-term follow-up due to potential subtle neurocognitive sequelae.